Comparative evaluation of three different glass ionomer cements - T Hari Sainath Reddy; K Vijay Venkatesh; Rekha Mani (Wolters Kluwer Medknow Publications, 2021)
Context: Newer glass ionomer cements with improved properties are constantly being developed. One such material is the novel Hybrid Glass-Ionomer cement (HGIC) with properties yet to be studied. Aims: The aim of this study was to compare the flexural strength, shear bond strength, wear resistance and fluoride release of Hybrid Glass Ionomer restorative with Conventional Glass Ionomer Cement (CGIC) and Resin modified Glass Ionomer Cement (RMGIC). Settings and Design: This was an in vitro study. Methods and Material: A total of 300 samples were tested in this study, with 100 samples per group and each group was further subdivided into 5 sub-groups with 20 samples each. Flexural and Shear bond strength values were determined by subjecting the specimens to a universal testing machine. For wear resistance, the specimens were assessed using a pin on the disc tribometer. For fluoride release, the test specimen suspended in 10 mL deionised water was tested at 24 h and 1 week. Statistical Analysis Used: One-way ANOVA. Results: RMGIC had the highest flexural and shear bond strength values followed by HGIC and CGIC. HGIC had the least wear rate followed by RMGIC and CGIC. At 24 h and 1 week, HGIC had the highest fluoride release among the study groups. Conclusions: HGIC exhibited the highest wear resistance and fluoride release among the cements studied. However, flexural and Shear bond strength values, of RMGIC, was comparatively higher.